Occupational Change among Nigerian Immigrants living in the Netherlands - Ijeoma, Pamela (African Human Mobility Review, 2021)
In this article, the term occupational change is used to refer to problems Nigerian skilled immigrants encounter in the Netherlands. Immigrants who may have had stable occupations or have attended higher education before migrating to the Netherlands face numerous difficulties including foreign qualification recognition, lack of Dutch language skills, and age factors in their search for jobs. They fall back to low cadre jobs as a way of survival in the Netherlands. I have explored the relationship between occupational change and stress among Nigerian immigrants who studied and worked in Nigeria before migrating to the Netherlands. First I argue that stress, which manifests as a result of occupational change amongst Nigerian immigrants in the Netherlands, is a clear reason for downward mobility amongst migrant children and their parents. Using the case of Nigerian skilled migrants in the Netherlands, I have designed a new framework that could be used to tackle issues of migrant occupational change as a result of foreign qualification recognition in host countries.